Metode Montessori untuk Mengatasi Kesulitan Membaca Siswa - Laely Aulia; Retno Nuzilatus Shoimah (AJER: Advanced Journal of Education and Religion, 2026)
Reading ability is a fundamental skill for Madrasah Ibtidaiyah students, as it serves as the foundation for understanding various subjects. Based on observations in grade II at MI Sabilul Huda, several students were found to experience reading difficulties, such as being slow in recognizing letters, struggling to pronounce syllables fluently, and lacking comprehension of simple texts. This study aims to examine the implementation of the Montessori method and its effectiveness in addressing reading difficulties, as well as to describe the improvement in students’ reading ability after the intervention. The research employed a quantitative approach with a single-subject experimental design type A–B. The subjects consisted of three grade II students selected through purposive sampling. Data were collected through reading tests (pretest and posttest), observation, and documentation, then analyzed using descriptive statistics, visual graphs, and PND (Percentage of Non-overlapping Data) analysis. The results showed that the Montessori method was implemented gradually, starting from letter recognition to reading short texts with comprehension, using concrete media such as letter cards, syllable cards, sandpaper letters, and picture books. The intervention improved the average reading score from 18.67 to 32.67 (an increase of 28% from the maximum score), with a PND of 100%, indicating very high effectiveness. Therefore, the Montessori method proved to enhance students’ fluency, accuracy, and independence in reading, and is considered a viable alternative strategy for teaching beginning reading at the elementary or Madrasah Ibtidaiyah level.